PSYCHOSOCIAL EDUCATIONAL FOR HEARING IMPAIRED CHILDREN IN LATVIA - Brokāne, Larisa; Zaiceva, Inamora (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article deals with the approach of psychosocial educational problems for hearing impaired children. These problems based on skill teaching and social interaction for hearing impaired children in Latvia. This review investigates the theories behind psychosocial educational and to be mostly based on psychoeducation theory. The findings of this review provide support for the use and further expansion of psychosocial educational interventions for hearing impaired children.